Dimensionamento de sistemas de aproveitamento de água pluvial utilizando energia fotovoltaica para edificações no Estado do Paraná, considerando futuros cenários de mudanças climáticas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The objective of this research was to evaluate rainwater harvesting systems and photovoltaic energy systems for three types of buildings (a single-family residence, a multifamily building and a broiler house) considering the current climate scenario and simulations of different scenarios of possible climate changes projected until the end of the century. The simulations were realized according to projections published on the IPCC’s Fifth Report and by local trends in of changes in air temperature and in the number of days without rain determined by statistical analyzes, which were Regression Analysis and Mann-Kendall Test, to verify the possibility of influence on the evaluated systems. Daily climatic data obtained from the National Meteorological Institute were used and the simulations were realized using the PGECLIMA_R software for eight localities of the State of Paraná, that were Campo Mourão, Castro, Curitiba, Irati, Ivaí, Londrina, Maringá e Paranaguá. For the dimensioning of the reservoirs of the rainwater harvesting systems were used the Brazilian Practical Method that is mentioned in the NBR 15527:2007, the method of consecutive dry days suggested by the Basic Sanitation Research Program and the methodology described by Embrapa. All localities showed the need to increase the size of the reservoir by the end of the century to supply the demand for non-potable water for the respective uses. This was evidenced in the simulation of the addition on the annual simulated rainfall regime and change in the number of dry days. In addition, for each type of building, a reservoir calculation methodology proved to be more coherent. The solar energy system for the single-family residence and for the multifamily building was designed only to supply the demand of the rainwater harvesting system. On the other hand, the photovoltaic panels of the aviary were dimensioned to supply not only the pumping system, but also the lighting and thermal control system of the environment. In all localities, the photovoltaic energy system proved to be efficient in meeting demand with percentages close to 100%, evidencing the fact Paraná has great potential for photovoltaic energy generation.
Keywords: Dimensionamento de reservatórios para água pluvial; Energia solar; Mudanças climáticas; Sustentabilidade; Sizing of rainwater reservoirs; Solar energy; Climate changes; Sustainability; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA